Dividing the Land: Time and Land Division in the English North Midlands and Yorkshire. (May 2022) - Griffiths, Seren; Johnston, Robert; May, Rowan; McOmish, David; Marshall, Peter; Last, Jonathan; Bayliss, Alex
Abstract : Land divisions are ubiquitous features of the British countryside. Field boundaries, enclosures, pit alignments, and other forms of land division have been used to shape and delineate the landscape over thousands of years. While these divisions are critical for understanding economies and subsistence, the organization of tenure and property, social structure and identity, and their histories of use have remained unclear. Here, the authors present the first robust, Bayesian statistical chronology for land division over three millennia within a study region in England. Their innovative approach to investigating long-term change demonstrates the unexpected scale of later 'prehistoric' land demarcation, which may correspond to the beginnings of increasing social hierarchy.